Communication and medial frontier crossings in the Jewish underground culture. - Smola, Klavdia (East European Jewish Affairs, 2018)
In this essay, the author examines Jewish art and literature in the context of the unofficial public sphere in the late Soviet Union. This Jewish cultural underground emerged within a specific communicative niche, which was the result of intensive private exchange, limited knowledge, and collectively discovered sources. The space in which artists and authors shared both their “work surface” and their coffee table, and in which the cultural production coincided with its own reception and analysis, constituted the cradle of very specific aesthetic features: particular forms of intertextual and intermedial links, self-reference, as well as a blend of the alternative lifeworld and art. Moreover, the close contact with “non-Jewish” artists in the same creative and often physical space brought about a synthetic form of culture. However, unlike with the Jewish vanguard artists of the first third of the twentieth century (such as the famous Kultur-lige), this synthesis was also caused by the largely non-Jewish socialization of “new Jews” in the late Soviet Union. This paper will focus on the following questions: How did the communicative context - the partial ban on Jewish topics and the alternative, semi-private public sphere of the Jewish unofficial culture in the late Soviet era - come about, and how did these aspects influence its artifacts?